Status of Common Serum Minerals and Trace Elements in COVID-19 Follow-up Cases: A Hospital-based Study from Eastern India - Saumyajit Maiti; Kheya Mukherjee; Debopriyo Samaddar; Debojyoti Bhattacharjee (National Journal of Laboratory Medicine, 2022)
Introduction: Management of post Coronavirus Disease-2019 (COVID-19) complications are the new challenges nowadays. It has been observed that in post COVID-19 cases the serum levels of several electrolytes and trace elements are deranged. Aim: This study was conducted to estimate the levels of different serum minerals and trace elements in one month post COVID-19 follow-up patients and compared with normal agesex matched controls. Materials and Methods: This hospital based cross-sectional study was conducted in the Department of Biochemistry in a tertiary care centre, over a period of six months (from January 2021 to June 2021). After fulfilling proper inclusion criteria, 223 COVID-19 follow-up patients of both genders (134 males and 89 females) were included as ‘case’ group. Age-sex matched 250 healthy volunteers were recruited as ‘control’ group. Levels of serum electrolytes (sodium and potassium) and trace elements (zinc, iron, calcium, phosphate, copper, magnesium and selenium) were estimated, analysed and compared against each other. Tables and statistical analysis was done using Statistical Package for the Social Sciences (SPSS) version 20.0. Results: In this study, the levels of serum zinc and iron were found to be higher and serum calcium, phosphate, copper, magnesium and selenium levels were reduced in post COVID-19 one month followup cases in comparison to controls. Female cases were in deficient state of iron, calcium, copper and magnesium but had high serum zinc and phosphate when compared to males. No abnormalities were noted in the level of electrolytes in post COVID-19 cases. Conclusion: Assessment and monitoring of levels of the mineral throughout the course of post COVID-19 follow-up is advisable for timely and appropriate measures to combat with post COVID-19 complications.